Evaluation of women referred to the two-week wait gynaecology clinic with suspected ovarian cancer. (November 2021) - Jeffery, H.E.; Gillespie, A.M.; Macdonald, M.
Abstract: Objectives: Ovarian cancer is the leading cause of death from gynaecological cancer in the UK, making early diagnosis key. The two-week wait pathway aims to facilitate rapid referrals from primary to secondary care for suspected cancer thus increasing rates of early diagnosis. The objective of this study was to evaluate referrals made via the two-week wait pathway for suspected ovarian cancer. Study Design: A retrospective analysis of 215 women referred on the two-week wait pathway to a tertiary centre in the United Kingdom with suspected ovarian cancer in 2018. Results: Only 16% of women referred were subsequently diagnosed with gynaecological malignancy. Of those diagnosed with ovarian cancer, 78% had late stage disease at diagnosis. Pre-menopausal women made up 29% of those referred, but only 6% of those diagnosed with cancer. Conclusion: Despite its goal of increasing early stage diagnosis of cancer, the majority of women referred via the two-week wait pathway do not have cancer, and the majority of those who do are referred with late stage disease. These results highlight the need for an effective screening programme for ovarian cancer.